Voyages in world history - Hansen, Valerie 1958-; Curtis, Kenneth Robert (Wadsworth Cengage Learning, 2014)
The authors of Voyages in world history never forget that history is made up of the stories of people. Each chapter of the text centers on a story--a traveler's account that highlights the book's main theme, the constant movement of people, goods, and ideas. The travelers include merchants, poets, rulers, explorers, soldiers, missionaries, and scholars, and their voyages provide a framework for each chapter that will draw you into the stories of world history. For the second edition of this text, the authors added broad global connections to every chapter, which will help you understand events in a larger context. The print text integrates with an online experience through the interactive Voyages Map App (fully accessible via any computer or mobile device), which will transport you virtually to the locations in the book to learn about the historic sites, and also includes a wealth of study tools. Voyages in world history helps you make sense of the range of people, places, and events crucial to comprehension of world history. -- Publisher.